E-Government-Based Public Service Innovations during the Covid-19 Pandemic at the Office of the Department of Population and Civil Registration in Keerom District - Hiskia C.M. Sapioper (Formosa Journal of Science and Technology, 2023)
This study aims to see and describe the service innovations that have been implemented by the Keerom Regency Population and Civil Registration Office in improving the quality of its services and the inhibiting factors. This research uses a descriptive qualitative approach. Data collection was carried out through observation, interviews, and documentation studies. The results of this study show the relative advantage of being able to shorten the process of service and document management; compatibility in general is compatible and not complicated for those who understand both employees and the community; the possibility of trial (trialability) of this online application has been tested and can help services quickly; in terms of convenience, it is very helpful for employees in facilitating the community compared to the old system.